Role of nutritional status in the early postoperative prognosis of patients operated for retroperitoneal liposarcoma (RLS): A single center experience. Issue 2 (February 2019) - Kirov, Krassen M.; Xu, Hao Ping; Crenn, Pascal; Goater, Philippe; Tzanis, Dimitri; Bouhadiba, Mohammed Toufik; Abdelhafidh, Khoubeyb; Kirova, Youlia M.; Bonvalot, Sylvie
Abstract: Purpose: To assess the nutritional status and its role in the outcome of patients operated for retroperitoneal liposarcoma (RLS). Material and methods: Retrospective study on consecutive patients operated with en bloc compartment resection for primary or local recurrence of RLS between 2016 and 2017. Preoperative nutritional and laboratory assessment comprising serum albumin, serum transthyretin, orosomucoid, and CRP was systematically performed. The following preoperative parameters were analysed: weight, body mass index (BMI), significant weight loss (>5% in one month and/or >10% in 6 months), serum albumin, transthyretin, CRP, orosomucoid. PINI (prognostic inflammatory and nutritional index) was calculated. Results: There were 40 patients operated for RLS: 22 women and 18 men with a median age of 61 years (34–90). Median tumour was 280 mm (80–530). Median preoperative BMI was 24.8 (18–42) and median postoperative BMI was 23 (17.8–44). Twenty-one patients (52.5%) were considered to be malnourished: 3 with biological signs of malnutrition and 18 with weight loss. Eleven (47.6%) in the group of malnourished patients and 4 (26.3%) in the group with satisfactory nutritional status developed postoperative complications (p = 0.042). A PINI score>1 was related to significantly longer hospitalisation time 21.8 days (10–58) in comparison with 14.9 [9–30] in patients with PINI < 1, p = 0.003. Conclusions: The malnourished patients with RLS experienced more postoperative complications and longer hospitalisation. Nutritional status and biological markers contribute to the global management of RLS with improved postoperative behaviour including fewer complications and shorter hospitalisation. A prospective larger study with longer follow-up is necessary to refine these results.